Gastric plexiform fibromyxoma tumor in a child - Case report and review of the literature - Michael W. Morris; Lisa Sullivan; David E. Sawaya; Michael A. Steiner; Michael J. Nowicki (Elsevier, 2016)
Plexiform fibromyxoma tumor (PFT) is an exceedingly rare tumor, particularly in children where only four cases have been reported to date. The patient reported herein presented with abdominal pain and vomiting related to gastric outlet obstruction caused by a large, polypoid PFT. We describe the clinical features, diagnostic evaluation, and surgical treatment of this rare tumor in our patient. Further, we review the literature of FPT to bring attention to this rare gastric tumor to the Pediatric Surgeon.